The Guardia Civil in the mirror: The impact of the Spanish gendarmerie model on the creation of the Guarda Nacional Republicana in Portugal, 1910-1926 - Vaquero Martínez, Sergio (Historia y Política, 2025)
The organization in Portugal of the Guarda Nacional Republicana during the First Republic (1910-1926) meant a milestone in the maintenance of public order because it became the first police with presence in the whole country. Although some scholars have pointed out the influence of some European gendarmerie models on this process, few studies have addressed this topic. This article analyzes the reception, reformulation and effect of the model of the Guardia Civil, and its impact on the foundation and deployment of the GNR. On the one hand, it studies the discourses on the Spanish gendarmerie with the aim of identifying the meanings and representations associated to the idea of the Guardia Civil, as well as the reconceptualization of the Spanish gendarmerie model. On the other hand, the article examines the public policies and legal regulations that shaped the GNR, comparing its characteristics with the Guardia Civil’s features in order to verify to what extent the Portuguese governments were inspired by the Spanish force. It concludes that the Guardia Civil archetype was a major reference in the design of the GNR. The republican elites used this institutional format in a strategic and selective manner, highlighting some of its attributes and removing others. Furthermore, the existence of a number of common traits in both forces that were not present in the French Gendarmerie allows to elaborate an Iberian gendarmerie model, understood as a variation of the ideal type of gendarmerie, which has been built on the French organizational matrix.
Keywords: Guarda Nacional Republicana; Guardia Civil; Portuguese First Republic; gendarmerie models; police circulations